Praktek Diplomasi Dari Peradaban Timur : India Kuno, China Kuno dan Islam - Denny Ramdhany (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2022)
The paper describes the development of diplomacy from the emergence of human civilization to the contemporary era. Expects in International Relations Studies have different perspectives regarding the sequence of development in the practice of Diplomatik Western writers tend to start discussing the evolution of diplomacy starting from the ancient Greek era by setting aside the Diplomatik thoughts and activities of eastern civilization, such as ancient India, ancient China, dan Islam. In fact, the three civilization also contributed greatly to both the thinking and the development of Diplomatik representation in 1961 adopting Kautilya’s ideas. Likewise ancient China thought contributed to aspect of international relations and Diplomatik. In Islam, Diplomatik is nont only related to worldly affairs, but also to matters of the hereafter. Therefore, diplomacy has strong historical roots in Islam. Based on this, the author will try to describe the thoughts of expects, especially regarding the practice of diplomacy in ancient India, ancient China, and Islam as additional references that have not been discussed by western thinkers.